Intentional Snake Road-Kill: A Case Study using Fake Snakes on a Brazilian Road. (September 2014) - Secco, Helio; Ratton, Pedro; Castro, Erika; da Lucas, Priscila Silva; Bager, Alex
Records of snakes are common in fauna road-kill monitoring studies in different Brazilian regions. To determine the intentionality of snake road-killing on a Brazilian road, the following hypotheses were tested: (1) more fake snakes are intentionally killed on the road than objects not similar to snakes; (2) the time elapsed until the first intentional fake snake road-kill is less than that for dissimilar objects; (3) the proportion of intentional collisions with fake snakes does not depend on the type of vehicle; (4) objects positioned in the center of the road are more frequently road-killed than those positioned on the roadside; (5) variation in the number of intentional road-kills is linked to variation of vehicular traffic. Fake snakes and PET bottles were placed in different positions on the MG-010 road (Minas Gerais State), and monitored for 96 hours by cameras that recorded the movement of vehicles on the lane. The numbers of intentional snake road-kills and control objects presented no differences, and the time elapsed until the first intentional road-kills was also similar. Cars and trucks are the vehicle categories with highest incidence of collisions. Objects were struck more often when positioned in the center of the road. This study proves that intentional road-killing occurs and that any small object on the road is subject to being struck by a moving vehicle. This behavior by some drivers on Brazilian roads may pose a threat to the conservation of species that venture onto these roads.